On the words ile in Dîvânu Lugâti’t-Türk and ayla in Kutadgu Bilig - SAĞOL YÜKSEKKAYA, GÜLDEN (My University, 2021)
Kutadgu Bilig is one of the most important treasures of Turkish history, art, language, and literature as well as Turkish cultural history, whereas Divanu Lugati\"t-Turk demonstrates the wealth of Turkish culture and civilization. Hundreds of studies have been done on these two works, yet they still pose many questions waiting to be answered. This article focuses on the word read as ila in Divanu Lugati\"t-Turk and Kutadgu Bilig and recommends a new way of reading it.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Sosyoloji; Social Sciences and Humanities; History; Sociology; TARİH; Sanat ve Beşeri Bilimler; Sanat ve Beşeri Bilimler (AHCI); ASYA ÇALIŞMALARI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); HISTORY; ARTS & HUMANITIES; Arts & Humanities (AHCI); ASIAN STUDIES; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Koruma; Sanat ve Beşeri Bilimler (çeşitli); Genel Sanat ve Beşeri Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Conservation; Arts and Humanities (miscellaneous); General Arts and Humanities; Social Sciences & Humanities; ila; ile; ayla; Divanu Lugati't-Turk; Kutadgu Bilig